EncounteredLimbs: A Room-scale Encountered-type Haptic Presentation using Wearable Robotic Arms - Horie, Arata; Saraiji, MHD Yamen; Kashino, Zendai; Inami, Masahiko (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2021)
Haptic information significantly improves human awareness of objects in virtual reality. One way of presenting this information is via encountered-type haptic feedback. An advantage of encounter type feedback is that it enables physical interaction with virtual environments without the need for specialized haptic devices on the hand. Additionally, encountered-type haptics are known for being able to provide high quality contact feedback to the user. However, such systems are typically designed to be grounded (i.e., fixed to the floor). As such, they typically have bounded workspace and a limited range of possible applications. In this work, we present a novel, wearable approach to presenting a user with encountered-type haptic feedback. We realize this feedback using a wearable robotic limb that holds a plate where the user might interact with their environment. An appropriate location for the plate is determined by a novel haptic solver while control of the arm is made possible using motion trackers. The system was designed to be stable, for presenting consistent haptic feedback, while also being safe and lightweight for wearability. By making the feedback system wearable, we enable the presentation of stiff feedback while maintaining the spatial freedom and unbounded workspace of natural hand interaction. Herein, we present the design of the novel system, mechanical and safety considerations when designing a wearable encountered-type system, and an evaluation of the system. A technical evaluation of the implemented system showed that the system provides a stiffness over 25 N/m and slant angle errors under 3°. Three user studies show the limitations of haptic slant perception in humans and the quantitative and qualitative effectiveness of the current prototype system. We conclude the paper by discussing various potentialapplications and possible improvements that could be made to the system.